The Relationship Between Self-Stigma, Basic and Instrumental Activities of Daily Living, and Communication Participation Among Individuals With Parkinson’s Disease - Ying Qian Ong; Nur Zahirah Zakaria; Jaehoon Lee; Chun Hong Gan; Siaw Chui Chai; Fierro Veronica; Fatimah Hani Hassan; Shin Ying Chu (SAGE Open)
The Malaysian healthcare system for individuals with Parkinson’s disease is still underdeveloped. Self-stigma has a significant influence on how successfully individuals with Parkinson’s disease handle their condition. Therefore, this study aimed to explore the association between self-stigma, basic and instrumental activities of daily living, and communication participation among individuals with Parkinson’s disease. In Study 1, 25 individuals with Parkinson’s disease from the Malaysian Parkinson’s Disease Association completed the Stigma Scale for Chronic Illness-8 Items, Katz Index of Independence in Activities of Daily Living, Lawton Instrumental Activities of Daily Living Scale, and Communicative Participation Item Bank. Survey responses were analyzed using descriptive statistics and correlation/regression. In Study 2, semi-structured interviews were conducted with nine individuals with Parkinson’s disease. Interview data were transcribed verbatim and analyzed using thematic analysis. Survey results indicated that a higher level of self-stigma was associated with lower levels of basic ( r  = −.47) and instrumental ( r  = −.21) activities of daily living and communication participation ( r  = −.41) among individuals with Parkinson’s disease. Furthermore, five main themes emerged from the in-person interviews: “challenges in performing activities of daily living due to Parkinson’s disease,” “speech and communication adaptations due to Parkinson’s disease,” “psychological responses toward one’s own Parkinson’s disease symptoms,” “self-stigmatization with impacts on self-concept,” and “perception formation of Parkinson’s disease resulting from self-stigmatization.” In conclusion, the self-stigma of individuals with Parkinson’s disease was considerably related to their activities of daily living and communication participation. Therefore, healthcare providers should address these factors collectively in their care of individuals with Parkinson’s disease. Moreover, health-related organizations and Parkinson’s disease associations must play a crucial role in educating and raising awareness of Parkinson’s disease in our society, considering that self-stigma is related to both how an individual perceives their condition and the public’s attitudes and perceptions toward it.